Quando não há cura, há religião? pessoas em cuidados paliativos em hospital do município de São Paulo - Palumbo, Isabel Cristina Bueno (2018)
This thesis aimed to analyze the meaning of religion for patients in palliative care and for their relatives. We start from the hypothesis that the approximation of religion and the development of religiosity and spirituality are fundamental to reduce the anguish provoked by the proximity of death among patients in palliative care and among their loved ones. It is an exploratory research of qualitative approach and historical method. To obtain the data, we conducted 11 interviews, 8 with patients and 3 with relatives of patients. The interviews were based on a semi-structured script with questions about the life history, religious experience and religion’s approach after the diagnosis of inability to cure. The interviews were realized at the Premier Hospital, on January 04th, 06th, 09th, 2017, and January 08th, 10th, 11th, 12th, 15th, 17th, 2018. During the month of December 2016, we visited the hospital every day to know the local routine and the hospitalized patients. For the construction of the script of questions and for the analysis of the data obtained from the interviews and the fieldwork, we adopted the historical method elaborated by Franz Boas (2004) and the hermeneutic analysis developed by Gadamer (1997). We also searched the history of the main concepts that guided our study. After analyzing and discussing the data of this research, we confirmed our hypothesis: we found that the majority of respondents came closer to religion after they were known to have incurable diseases